2002
DOI: 10.1034/j.1600-0420.2002.800409.x
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide reduces ischaemia‐reperfusion injury in the retina

Abstract: ABSTRACT.Purpose: To investigate the role of octreotide on retinal lipid peroxidation and histopathological changes during ischaemia/reperfusion (I/R). Methods: Three groups of seven pigmented guinea pigs each were formed. These represented a control group, an ischaemia group and an ischaemia/octreotide group. One eye of each animal was selected for histopathological evaluation and the other for biochemical assay. Bilateral pressure-induced retinal ischaemia was instigated for 90 min and was followed by 24 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
4
13
0
Order By: Relevance
“…It was also efficient in reversing retinal cell death as observed with the TUNEL assay [103]. Comparable results were also observed in an earlier study where octreotide reduced the increase of lipid peroxidation levels observed subsequent to ischemia/reperfusion retinal injury [106]. In agreement with these data, the increased presence of functional sst 2 receptors, in retinas of sst 1 k.o.…”
Section: Ex Vivo Studiessupporting
confidence: 80%
“…It was also efficient in reversing retinal cell death as observed with the TUNEL assay [103]. Comparable results were also observed in an earlier study where octreotide reduced the increase of lipid peroxidation levels observed subsequent to ischemia/reperfusion retinal injury [106]. In agreement with these data, the increased presence of functional sst 2 receptors, in retinas of sst 1 k.o.…”
Section: Ex Vivo Studiessupporting
confidence: 80%
“…It has been indicated that OCT was associated with the integrity of blood vessel endothelium, as confirmed by previous studies (14)(15)(16). Damage of endothelial cells is often observed in the early stage of DR (3,17,18).…”
Section: Discussionsupporting
confidence: 62%
“…This will lead to an increase in the whole retinal and sub‐layer thickness. Along with the edema and inflammatory reaction, the neuronal injury will be aggravated (decrease in the number of cells) and lead to the reduction of retinal thickness at 7 days after retina I/R . For the retinal I/R injury, our results corresponded to those of previous reports.…”
Section: Discussionmentioning
confidence: 62%